The Strategic Analysis of Managing Raw Material Replenishment for Product-based Manufacturing System - M.K.S, Shafei; M.N, Che-Ani; I.A, Azid (International Journal of Engineering and Technology, 2018)
The product-based manufacturing system is widely applied in manufacturing industries based on the segregation of products and it is mostly designed based on the human dependent processes. To ensure the smoothness of production processess, the raw material replenishment activity plays an important role in terms of avoiding the material shortage. Currently, several concepts have been designed for material replenishment but the issue of material shortage in manufacturing system still occurs and it has interrupted the flow of production processes due to quality issue and production lead time. Thus, the present study investigates and examines the selected concepts in raw material replenishment to determine the optimum solution material replenishment concept. Three concepts of the material replenishment system were identified, namely adhoc, self-service and dedicated, and all of these concepts were examined in terms of waiting time. The result showed the dedicated concept was identified as the greatest concept of managing the material replenishment for product-based manufacturing system.